A review of comprehensive post-occupancy evaluation feedback on occupant-centric thermal comfort and building energy efficiency - Zhao, Jing; Abdul Aziz, Faziawati; Deng, Yiyu; Ujang, Norsidah (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The post-occupancy evaluation process is pivotal for assessing the performance of indoor and outdoor living environments after occupation. This evaluation involves a multifaceted analysis, encompassing energy efficiency, indoor environmental quality, outdoor spaces, and occupant satisfaction. Despite the inherent advantages and potential applicability of post-occupancy evaluation in residential buildings, the lack of uniformity in research methodologies, data collection techniques, investigative approaches, and result interpretation has impeded cross-comparisons and method replication. In a concerted effort to enhance the understanding of prevailing post-occupancy evaluation methodologies, this study undertook a comprehensive systematic literature review of post-occupancy evaluation practices within the residential domain from 2000 to 2023. The results unequivocally underscored the pervasive lack of consistency in methodological applications, tool deployment, and data reporting across diverse post-occupancy evaluation investigations. The objectives of this review aimed to examine the existing post-occupancy evaluation (POE) methods, assess occupant-centric thermal comfort, evaluate the impact of POE feedback on building design, and develop recommendations for architects, engineers, facility managers, and policymakers on leveraging POE feedback to enhance thermal comfort and energy efficiency in buildings. This study offers critical insights into advocating for a more standardized and cohesive post-occupancy evaluation approach. The findings of this review can direct the establishment of a coherent and consistently implemented post-occupancy evaluation framework within the realm of residential architecture.